DETERMINANTS OF THE QUALITY OF FINANCIAL REPORTS OF THE LOCAL GOVERNMENT OF JEMBER DISTRICT - Athallah, Zidan Dhia; Widajantie, Tituk Diah (International Journal of Economy, Education and Entrepreneurship (IJE3), 2023)
To maintain the public's trust in the government, public institutions must improve the quality of the services they provide to the general public. The presentation of excellent financial reports is one example of such an enhancement. To ascertain how internal control mechanisms, information technology use and human resource competency impact the calibre of financial statements, this research's case study on the Regional Apparatus Organization (OPD) of the Jember Regency Regional Government. The quantitative study's approach to collecting data is the survey method. The study's primary sources were questionnaire responses, providing preliminary data. The sample in this research consisted of 100 participants in the analysis method. This research demonstrates that the usage of information technology (X2), internal control systems (X3), and HR management abilities (X1) all have a substantial and beneficial influence on the financial report's quality. After considering the R2 values of 52.6% and 47.4%, additional elements influence the quality of the financial statements